Exploring the New Testament: the letters and revelation - Marshall, Howard; Wenham, David (London : SPCK, 2021)
Especially suited for introductory courses that focus on Jesus and the Gospels or the Gospels and Acts, Exploring the New Testament, Volume one introduces students to: Jewish and Greco-Roman backgrounds, literary genres and forms, debated issues such as authorship, date and setting, content and major themes of each book, conventional as well as new approaches to the study of the Gospels and Acts, the latest scholarship in the quest for the historical Jesus, and the intersection of New Testament criticism with contemporary faith and culture.
v. 1. Guide to the Gospels & Acts / David Wenham & Steve Walton -- v. 2. Guide to the Letters & Revelation / I. Howard Marshall, Stephen Travis & Ian Paul.
Includes bibliographical references and index.
Keywords: Bible. -- Textbooks; Textbooks